Intraarterial Transplantation of Mitochondria After Ischemic Stroke Reduces Cerebral Infarction - Pedro Norat; Jennifer D. Sokolowski; Catherine M. Gorick; Sauson Soldozy; Jeyan S. Kumar; Youngrok Chae; Kaan Yagmurlu; Joelle Nilak; Khadijeh A. Sharifi; Melanie Walker; Michael R. Levitt; Alexander L. Klibanov; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Background Transplantation of autologous mitochondria into ischemic tissue may mitigate injury caused by ischemia and reperfusion. Methods Using murine stroke models of middle cerebral artery occlusion, we sought to evaluate feasibility of delivery of viable mitochondria to ischemic brain parenchyma. We evaluated the effects of concurrent focused ultrasound activation of microbubbles, which serves to open the blood–brain barrier, on efficacy of delivery of mitochondria. Results Following intraarterial delivery, mitochondria distribute through the stroked hemisphere and integrate into neural and glial cells in the brain parenchyma. Consistent with functional integration in the ischemic tissue, the transplanted mitochondria elevate concentration of adenosine triphosphate in the stroked hemisphere, reduce infarct volume and increase cell viability. The addition of focused ultrasound leads to improved blood–brain barrier opening without hemorrhagic complications. Conclusion Our results have implications for the development of interventional strategies after ischemic stroke and suggest a novel potential modality of therapy after mechanical thrombectomy.